2012
DOI: 10.1039/c2cp42066j
|View full text |Cite
|
Sign up to set email alerts
|

The conversion of CO2 and CH4 to acetic acid over the Au-exchanged ZSM-5 catalyst: a density functional theory study

Abstract: The direct conversion of methane and carbon dioxide to acetic acid is one of the most challenging research topics. Using the density functional theory (M06-L) the study reveals the catalytic activity of the Au(I)-ZSM-5 zeolite in this reaction. The Au(I)-ZSM-5 is represented by a 34T quantum cluster model. The activation of the C-H bond over the Au-ZSM-5 zeolite would readily take place via the homolytic σ-bond activation with an energy barrier of 10.5 kcal mol(-1), and subsequent proton transfer from the Au c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 59 publications
(57 reference statements)
2
53
0
Order By: Relevance
“…To illustrate distinct catalytic performance on chemical fixation of CO 2 to propylene carbonate catalyzed by these constructed MOFs with different metal centers, molecular dynamic simulations were conducted . First, the C atom of CO 2 molecule is sp hybridized, which can form σ bond with O atom.…”
Section: Resultsmentioning
confidence: 99%
“…To illustrate distinct catalytic performance on chemical fixation of CO 2 to propylene carbonate catalyzed by these constructed MOFs with different metal centers, molecular dynamic simulations were conducted . First, the C atom of CO 2 molecule is sp hybridized, which can form σ bond with O atom.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, [11] we have shown that the adsorption of CO 2 over Au I -ZSM-5 is less favorable than that of methane in the acetic acid production and that methane activation is needed in the first step of the reaction. Without catalyst, the direct conversion of methane and carbon dioxide to carboxylic acid is kinetically very unfavorable with an E a of 83.8 kcal mol À1 , as calculated at the M06 L/ 6-31G(d,p) level, or 87.6 kcal mol À1 if calculated at the MP2/6-31G(d,p) level of theory.…”
Section: Càh Activation Of Ethanementioning
confidence: 98%
“…lite to produce acetic acid [11] has been demonstrated theoretically. However, this process requires high activation energy.…”
Section: Introductionmentioning
confidence: 97%
“…However,t he knowledge about CÀCcoupling between CH 4 and CO 2 is very limited owing to the difficulty to identify active species to simultaneously activate and couple these two substrates. [3,13] Recently,T rinh and co-workers predicted that boron-doped copper is apotential catalyst to activate methane to form the absorbed CH x (x = 2, 3) on the catalytic surface and selectively promote the C À Cc oupling reaction to produce ethylene. [12] Herein, we present the first example of diatomic species (CuB + )t hat can also couple CH 4 and CO 2 to form H 2 C = C = Ou nder thermal collision conditions.…”
mentioning
confidence: 99%